PROSES PEMECAHAN MASALAH MATEMATIKA SISWA SMA BERDASARKAN KECERDASAN MAJEMUK - Sumadi, Suhartini; Putra, Teguh Yuliandri; Astutik, Heny Sri (Journal of Honai Math, 2020)
This study aims to analyze the mathematics problem-solving process of high school students based on multiple intelligences. In research, multiple intelligence is divided into dominant linguistic intelligence, interpersonal and kinesthetic intelligence, dominant musical intelligence, logical-mathematical and naturalistic, existential, intrapersonal, and visual dominant intelligence. The type of research used in this research is descriptive exploratory, and the approach used is qualitative and quantitative approaches. Determination of research subjects was carried out using purposive sampling based on multiple intelligences, to obtain 3 high school students of class X as research subjects. The research instrument used was a multiple intelligence test and two problem-solving tests adopted from the American High School Math Exam (AHSME) Problems and the Provincial High School Mathematics National Science Olympiad questions. The data obtained were analyzed, utilizing data reduction. The research results show that students with multiple different intelligence bits have different ways of solving them, but there are also similarities in solving problems.